Survival, physical and physiological changes of Taenia hydatigena eggs under different conditions of water stress - Sánchez Thevenet, Paula (2017)
Taenia hydatigena eggs were investigated for morphological and physiological changes under water stress conditions. Fresh eggs were exposed at 31%, 47% and 89% of relative humidity (RH), and survival, size and ultrastructural changes were accounted up to 365 days of exposition. The article shows how each RH environment affects the vitality of the eggs. Results of this study suggest that T. hydatigena eggs have mechanisms to withstand water stress, indicating that the eggs clustering improves protection against desiccation, and that endogenous metabolism using triacylglycerols play an important role in the maintenance of embryo vitality under low, medium and high relative humidity conditions. This contributes to understanding the water stress resistance mechanism in eggs belonging to Taeniidae family. The findings shown herein have provided a basis to better comprehend basic biology and epidemiology of the cysticercosis caused by T. hydatigena.